The effect of prenatal alcohol exposure (PAE) on the onset of speech disorders and communication problems in children and adolescents - Gryc, Anna; Lipiec, Jakub; Grudzień, Monika; Golemo, Jagna; Świdziński, Rafał (Journal of Education, Health and Sport, 2022)
Alcohol consumption has many negative effects on the human body, and has been proven to have teratogenic effects on fetal development. Prenatal alcohol exposure (PAE) is associated with growth deficits and neurodevelopmental disorders, including fetal alcohol spectrum disorder (FASD). Despite such effects, there are still many women who do not give up the consumption of alcoholic beverages during pregnancy. This article, based on a review of available studies on PubMed, examines whether prenatal alcohol exposure can cause problems in children's speech development and promote communication problems in children, as well as in adolescents. Longitudinal observations on prenatal alcohol exposure (PAE) have shown that children up to the age of 3 after PAE have difficulties in receptive or expressive communication compared to a group not prenatally exposed to alcohol. Alcohol has been shown to be the overriding factor causing disorders in the development of the brain and nervous system, which are the main structures responsible for the process of speech development and also the formation of communication skills. Studies among adolescents with PAE have shown that they have weaker spoken and written language skills than those without PAE or with low PAE. This also translates into difficulties in developing their communication skills, which can make it much more difficult for them to become independent and move smoothly through the difficult period of adolescence.